Qur’anic Therapy (Islamic Bibliotherapy) To Improve Religious Coping In Hemodialysis Patient - Inggriane Puspita Dewi; Anggriyana Tri Widiyanti (Universitas Muhammadiyah Semarang, 2018)
Patients with chronic kidney disease and receiving hemodialysis, they will deal with chronic stress related to time restriction, financial and functional limitations, dietary restrictions, and drug side effects. The purpose of the present study was to determine the effect of psychoreligius therapy: Qur'anic therapy (Islamic bibliotherapy) on the religious coping of hemodialysis patients. The study was conducted at Al-Islam Bandung Hospital used pre-experimental with pre and post-test design. We used purposive sampling, 22 sample, they were 5 years undergoing hemodialysis, able to read and Muslim. Psychological Measure of Islamic Religiousness (PMIR) to measure religious coping with a correlation coefficient of 0.88. ). The sample was given reading with sincere themes, patience, gratitude according to al-Qur' values for 1 month (8 reading themes), about 30 minutes, religious coping measured before and after the intervention. There was a significant effect of the intervention of Quranic therapy on religious coping (p = 0.048 , the analysis used Paired T-test. Islamic psychoreligius Therapy: Qur'anic Therapy promoted to improve religious and coping skills in hemodialysis patients through Quranic Therapy. Therefore, in cases of chronic diseases such as chronic renal failure, nurses should apply a holistic care approach with emphasis on spirituality-based intervention.